PENINGKATAN KAPASITAS PELAYANAN PENANGANAN STROKE ISKEMIK AKUT MELALUI PELATIHAN CODE STROKE DI RS UNIVERSITAS MATARAM - Ilsa Hunaifi; Dewi Suryani; Mohammad Rizki; Didit Yudhanto; Triana Dyah Cahyawati; Herpan Syafii Harahap; Muhammad Ghalvan Sahidu (Universitas Mataram, 2023)
Stroke is the leading cause of death and disability in the world and Indonesia. The standard therapy for acute ischemic stroke is alteplase but only 10-20% of patients receive this standard therapy. Code stroke is quick response for management acute stroke to get alteplase. The success for code stroke requires good communication and cooperation of code stroke team. This training aims to provide code stroke training needed to increase the capacity of stroke services at Mataram University Hospital. The method of training include lecture, patient simulation, video on the code stroke and also preparation of the thrombolysis also discussion and the target of this training are doctors and staffs in the emergency wards, radiology, laboratorium, pharmacy, ICU and inpatient ward. Evaluation of participants' understanding through pre and post tests was assessed with the Kahoot application. Evaluation of the training was also assessed using the Google form. A total of 25 health workers participated in this activity. The mean pre and post test were 34,38% and 68,42% (an increase of 34%). Participants' satisfaction with the activity was good, namely 4.13 (from a Likert scale of 0 – 5). The aspect of material provided in this training had the highest satisfaction score. This education should be given periodically to all health workers to increase the capacity of stroke services.